Modern pollen vegetation relationships in a dry deciduous monsoon forest: A case study from Lonar Crater Lake, central India. (12th June 2015) - Riedel, Nils; Stebich, Martina; Anoop, Ambili; Basavaiah, Nathani; Menzel, Philip; Prasad, Sushma; Sachse, Dirk; Sarkar, Saswati; Wiesner, Martin
Abstract: As part of ongoing research on Holocene lacustrine sediments of Lonar Crater Lake (central India), pollen assemblages in lake surface sediment and soil samples were studied to unravel pollen–vegetation relationships, including pollen transport processes in tropical dry deciduous forest vegetation. Furthermore, palynological results were compared with geochemical proxies and spatial features of the lake sediments and the vegetation. The obtained data reveal strong differences in pollen assemblages and pollen concentrations between and within the studied trapping media. Local arboreal vegetation is adequately represented in the soil samples, but is less represented in the lake surface sediment samples. The composition of the lacustrine pollen assemblages is mainly influenced by patterns of transport through surface and channel runoff. Besides the relevance of our new data for reliable interpretation of fossil pollen spectra extracted from Lonar sediment cores, the results of this study are of general importance for the understanding of Quaternary pollen assemblages from tropical lacustrine archives, as well as for the implementation and selection of suitable approaches for quantitative pollen based environmental reconstructions in south Asia and beyond.